The importance of responsibility in self-educational activity of students of machine-building specialties in quarantine conditions - Kravtsova, N. V. (Національний технічний університет "Харківський політехнічний інститут", 2021)
The article focuses on the problem of proper self-educational activity of future bachelors of mechanical engineering specialties. It is emphasized that in technical institutions of higher education, while sufficient pedagogical interaction is impossible under conditions of quarantine restrictions, the responsibility of students is significantly important. The problem of the lack of full-fledged pedagogical control with the dominance of online and hybrid forms of education increases the probability (during completing individual assignments) of students’ writing-off from Internet sources, thereby, fabrication, falsification, and embezzlement of someone's studies, conclusions and opinions, what contributes to the presence of plagiarism in students' works and is strictly prohibited in the Law of Ukraine "On Higher Education". The important role of responsibility in the independent activity of students during the pandemics has been proven.

В статті акцентовано увагу на проблемі належної самоосвітньої діяльності майбутніх бакалаврів машинобудівних спеціальностей. Підкреслено, що в технічних закладах вищої освіти при неможливості достатньої педагогічної взаємодії за умов карантинних обмежень відповідальність студентів набуває особливого значення. Проблема відсутності повноцінного педагогічного контролю при домінуванні онлайн та змішаних форм навчання підвищує ймовірність (при оформленні індивідуальних домашніх завдань) практики списування студентами з інтернет-джерел, тобто фабрикацію, фальсифікацію та присвоєння чужих досліджень, висновків та думок, що означає наявність плагіату в роботах студентів та категорично заборонено в Законі України "Про Вищу освіту". Доведено важливу роль відповідальності під час самостійної діяльності студентів в умовах пандемії.
Важливість відповідальності у самоосвітній діяльності студентів машинобудівних спеціальностей в умовах карантину
Keywords: competence; pandemic events; independent work; компетентність; майбутні бакалаври машинобудівних спеціальностей; пандемічні заходи; самостійна робота